О связях между энергопотреблением и экономическим ростом: аналитический обзор - Череватский, Д.Ю.; Чекина, В.Д. (Економіка промисловості, 2015)
Статья посвящена актуальной проблеме анализа литературных источников, рассматривающих связи потребленияпервичных энергетических ресурсов и экономического роста национальных экономик. Проанализированы количественные и характерологические различия в научных трудах украинских, российских исследователей и ученых из дальнего зарубежья. Доказана ущербность подхода, основанного на использовании существующих методов математической статистики, целесообразность отраслевой декомпозиции наблюдений и учет активности теневой деятельности в разных отраслях национальной экономики. Стаття присвячена актуальній проблемі аналізу літературних джерел, у яких розглядаються зв'язки споживанняпервинних енергетичних ресурсів та економічного зростання національних економік. Проаналізовано кількісні та характерологічні відмінності в наукових працях українських, російських дослідників і вчених із далекого зарубіжжя. Доведено ущербність підходу, заснованого на використанні існуючих методів математичної статистики, доцільність галузевої декомпозиції спостережень й урахування активності тіньової діяльності в різних галузях національної економіки. The modern civilization represents a compromise of three "E"-economy, environment and energy. Given that, the economical and environmental components are a direct function of the consumption of primary energy resources (PER), this factor is crucial. The emergence of a new scientific discipline - an economic energetics, the publication of a number of specialized magazines, several thousands related publications - gives evidence of the importance of energetic ensuring of economic growth of national economies and sustainable human development. In this context a relatively small number of themed publications in the former Soviet Union and the countries of the former communist block seem paradoxical. Besides that, the scientific researches of Ukrainian and Russian experts are different: they are mostly devoted to the energetic component and much less affect its relationship with economic growth. These disproportions have induced the researchers to perform a general review of articles of national and foreign authors. In the process of literary sources studying it was found that the main subject of research abroad is the test of four hypotheses about connection between two variables: EC (Energy Consumption) and GDP (Gross Domestic Product) - the variables don‟t correlate; the growth of energy consumption causes the economic growth; the economic growth stimulates the energy consumption; mutual development exists. For test of these hypotheses foreign analysts use the complex mathematical tool. In domestic practice such statistical methods in the evaluation of the economic and energetic connections are rarely used. Despite the long-term and significant efforts to identify the links between economic growth and primary energy resources consumption, research results are very contradictory. In general, since the 1990s, the debate on the issue has degenerated into a debate about the legality of the metamathematical statistics methods. Recently many scientists tend to the shift problem solving strategy to the expanse of attention to the institutional factors influence, particularly to the accounting on the informal sector activity. Discussion points are present among Russian scientists as well. Some of them are of the opinion based on the dependence of energetic consumption in Russia on the geographic rather than economic factors, others defend the economic motivation of energy consumption, and the uncertainty of results obtained is explained by insufficient development of the country's market-based mechanisms. In Ukrainian analytics the approach to the practical requirements generation of PER is prevalent on the assumption of existing reality. Neither Russian nor Ukrainian studies do not connect consumption of PER with the influence on the informal sector. The conclusion concerning the reasonability of consideration of economic and energetic problem was made by sectoral decomposition of economic processes and accounting of distinctions in terms of informal activities.